The Mediating Role of Work Engagement in the Relationship between Job Crafting and Turnover Intention: Evidence from Kab. Tegal SMEs - Elfa Umami; Putri P; Akih Putri; Ismail Muhamad; Yoga Ferdiansah; Mei Amalia (Penerbit Jurnal Indonesia, 2025)
This study aims to examine the effect of job crafting on turnover intention with work engagement as a mediating variable among employees of Small and Medium Enterprises (SMEs) in Tegal Regency. High turnover intention in the SME sector has become a critical issue as it negatively affects organizational stability and business sustainability (Halbesleben & Wheeler, 2008). Theoretically, job crafting and work engagement are believed to reduce employees' intention to leave; however, empirical findings in the context of Indonesian SMEs remain inconsistent (Bakker et al, 2012). This study employs a quantitative approach with an explanatory research design. Data were collected through questionnaires using a 5-point Likert scale, supported by observations and interviews, involving 31 SME employees in Tegal Regency. Data analysis was conducted using linear regression and the Sobel mediation test to examine the effect of job crafting on turnover intention, the effect of job crafting on work engagement, and the mediating role of work engagement in the relationship between job crafting and turnover intention. The results indicate that job crafting has no significant effect on turnover intention (β = 0.001; sig = 0.978) and no significant effect on work engagement (β = –0.105; sig = 0.177). Furthermore, work engagement has no significant effect on turnover intention (β = 0.154; sig = 0.140). The Sobel test result shows a Z value of 0.0227 with a significance level of p = 0.9818 (> 0.05), indicating that work engagement does not mediate the relationship between job crafting and turnover intention. These findings suggest that efforts to enhance job crafting and work engagement alone are insufficient to reduce turnover intention among SME employees without adequate organizational support (Demerouti et al, 2001).